Integrating Social Education with Digital Literacy in Schools - Mustafa Habib (JELIM : Journal of Education, Language, Social and Management, 2026)
This study aims to explore the integration of social education with digital literacy in school settings and examine its impact on students’ social and digital competencies. In the context of rapid technological advancement, students are required not only to master digital skills but also to demonstrate responsible and ethical behavior in online environments. Therefore, integrating social education with digital literacy becomes essential in preparing students for the challenges of the 21st century. This research employed a qualitative approach, involving teachers and students selected through purposive sampling. Data were collected through classroom observations, semi-structured interviews, and document analysis. The data were analyzed using thematic analysis to identify patterns related to instructional strategies, student engagement, skill development, and implementation challenges. The findings reveal that the integration of social education with digital literacy enhances student engagement, promotes critical thinking, and fosters responsible digital behavior. Students demonstrated improved collaboration, communication, and ethical awareness when engaging in digitally supported social learning activities. In addition, teachers played a crucial role in facilitating meaningful learning experiences and guiding students in applying social values within digital contexts. However, challenges such as limited technological resources, unequal access to digital tools, and lack of teacher training were identified as barriers to effective implementation. In conclusion, integrating social education with digital literacy is a relevant and effective approach to developing students’ competencies in the digital era. It is recommended that educational institutions provide adequate support, training, and resources to ensure the successful implementation of this integrated learning approach.